Cs+ removal and optical detection by microporous lanthanide silicate Eu-AV-20 in a fixed-bed column - Figueiredo, Bruno R.
Microporous silicate Eu-AV-20 has recently proved to be a promising ion exchange material for cesium removal from aqueous solutions, and its potential for Cs+ photoluminescence sensing was additionally demonstrated. In this work, Cs+ removal was performed in a fixed-bed column, and the influence of linear velocity and mass of ion exchanger on the breakthrough curves was analysed. The experimental data were modelled on the basis of Nernst-Planck (NP) equations and with four well-known analytic models. The analytic expressions provided low errors (root mean square deviation, RMSD, between 3.20% and 6.47%); the 2-parameter NP-based model fitted the data quite well (RMSD = 6.66% for correlation and 6.54% for prediction), yielding crucial information on both the transport mechanism within the Eu-AV-20 particles, and the intrinsic dynamic behaviour of the fixed-bed ion exchange column. Taking into account that Eu-AV-20 samples loaded with different amounts of Cs+ exhibited distinct photoluminescence spectra, our results reinforce the potential of AV-20 materials for Cs+ sensing, which raises the possibility of online monitoring the ion exchange in a fixed-bed column using an optical fibre and a spectrometer. (C) 2015 Elsevier B.V. All rights reserved.